2021
DOI: 10.3390/nu13082558
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Vitamins and the Risk of Offspring Autism Spectrum Disorder: Systematic Review and Meta-Analysis

Abstract: Prenatal nutrition is associated with offspring autism spectrum disorder (herein referred to as autism), yet, it remains unknown if the association is causal. Triangulation may improve causal inference by integrating the results of conventional multivariate regression with several alternative approaches that have unrelated sources of bias. We systematically reviewed the literature on the relationship between prenatal multivitamin supplements and offspring autism, and evidence for the causal approaches applied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, a reduced risk was observed in the subgroup of high-quality observational studies (RR = 0.77; 95% CI, 0.62 to 0.96; p < 0.05; I 2 = 62.4%), studies focused on early pregnancy (RR = 0.76; 95% CI, 0.58 to 0.99; I 2 = 79.8%), and prospective studies (RR = 0.69, 95% CI, 0.48 to 1.00; I 2 = 95.9%). 44 More specifically, folic acid supplementation during early pregnancy was associated with a lower risk of offspring's ASD (k = 10; n = 9,795 ASD cases; OR = 0.57; 95% CI, 0.41 to 0.78). The consumption of a daily amount of at least 400 μg folic acid from dietary sources and supplements, was associated with a reduced risk of offspring ASD (k = 1; n = 466; OR = 0.55; 95% CI, 0.36 to 0.83).…”
Section: Results Of Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a reduced risk was observed in the subgroup of high-quality observational studies (RR = 0.77; 95% CI, 0.62 to 0.96; p < 0.05; I 2 = 62.4%), studies focused on early pregnancy (RR = 0.76; 95% CI, 0.58 to 0.99; I 2 = 79.8%), and prospective studies (RR = 0.69, 95% CI, 0.48 to 1.00; I 2 = 95.9%). 44 More specifically, folic acid supplementation during early pregnancy was associated with a lower risk of offspring's ASD (k = 10; n = 9,795 ASD cases; OR = 0.57; 95% CI, 0.41 to 0.78). The consumption of a daily amount of at least 400 μg folic acid from dietary sources and supplements, was associated with a reduced risk of offspring ASD (k = 1; n = 466; OR = 0.55; 95% CI, 0.36 to 0.83).…”
Section: Results Of Synthesesmentioning
confidence: 99%
“…In the field of nutritional psychiatry in children and adolescents, the most extensively studied mental disorders are ASD, [43][44][45][46][47][48][49][50][51][52][53] followed by ADHD. [34][35][36][37][38][39][40][41][42] These results are consistent with the observed increase in the prevalence of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal malnutrition following famine exposure has also been strongly associated with risk of psychotic disorders 65 , notwithstanding similar issues around causality. A systematic review also found evidence to support a protective effect of prenatal multivitamin supplementation on autism spectrum disorder 74 , but this was restricted to high‐quality studies. Surprisingly few studies have examined the association between prenatal nutrition and common mental disorders, with no systematic review available, although some longitudinal evidence exists for childhood mood and behavioural outcomes 75‐77 , with associations persisting after adjustment for maternal perinatal mental health, prenatal smoking and alcohol use.…”
Section: Social Determinants That Impact Mental Health and Disorder: ...mentioning
confidence: 99%
“…There is a wide recognition that the etiology of ASD is multifactorial, involving the interplay of genetic and environmental factors [2]. Strong evidence has suggested that ASD is influenced by prenatal factors [3] including maternal nutrition [4]. Specific nutrients have been identified as potentially impacting the risk for ASD, for example, folate, vitamin D, iron and polyunsaturated fatty acids, but the findings are often mixed [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…1 Data missing for 6 controls; 2 Data missing for 8 controls;3 Data missing for 6 controls;4 Data missing for 6 controls;5 Data missing for 8 controls.…”
mentioning
confidence: 99%